UJI EFEKTIVITAS PUPUK CAIR AZZOLA MICROPHYLLA DAN PUPUK ORGANIK TAKAKURA TERHADAP PERTUMBUHAN TANAMAN SAWI (Brassica juncea) - Zakiyah Amini; Dina Dwirayani; R. Eviyati (Jurnal Ilmiah Hijau Cendekia, 2022)
This research was aims to examine the effectiveness of application of liquid organic fertilizer Azzolla Microphylla and organic fertilizer takakura on the growth and yield of mustard greens (Brassica juncea. Azzola as a green manure can improve the chemical properties of the soil because it can meet the nitrogen needs of plants . Giving nitrogen to plants can accelerate plant growth , especially stems and leaves . The N content of Azolla liquid fertilizer can stimulate plant growth . Giving Azolla microphylls as a liquid organic fertilizer is more easily absorbed by plants so that plant growth can be optimal . In this study , observing the effect of applying liquid organic fertilizer Azolla microphylls on sweet mustard greens using Takakura organic compost media at the age of 21 , 28 , and 39 DAP with the observed variables being the number of leaves , leaf length and width and the variables observed after harvest . including weight of consumption and volume of roots . The results of this study showed that there was no significant effect of / on the application of liquid zols fertilizer and Takakura fertilizer on the number of leaves , length and width of the mustard greens (Brassica juncea ) at 21 , 28 , and 39 days after planting (HST ) between zols liquid fertilizer and Takakura fertilizer . The application of Azolla fertilizer and Takakura growing media had a significant effect on the consumption weight of mustard (Brassica juncea ) plants . It can be seen that the consumption weights of T3 , T3 , T1 and T4 have a high value compared to T0 or without fertilizer application .